Environmental Factors Controlling the Distribution of Symbiodinium Harboured by the Coral Acropora millepora on the Great Barrier Reef - Cooper, Timothy F. (Public Library of Science, 2011)
BACKGROUND: The Symbiodinium community associated with scleractinian corals is widely considered to be shaped by seawater temperature, as the coral's upper temperature tolerance is largely contingent on the Symbiodinium types harboured. Few studies have challenged this paradigm as knowledge of other environmental drivers on the distribution of Symbiodinium is limited. Here, we examine the influence of a range of environmental variables on the distribution of Symbiodinium associated with Acropora millepora collected from 47 coral reefs spanning 1,400 km on the Great Barrier Reef (GBR), Australia. METHODOLOGY/PRINCIPAL FINDINGS: The environmental data included Moderate Resolution Imaging Spectroradiometer (MODIS) satellite data at 1 km spatial resolution from which a number of sea surface temperature (SST) and water quality metrics were derived. In addition, the carbonate and mud composition of sediments were incorporated into the analysis along with in situ water quality samples for a subset of locations. Analyses were conducted at three spatio-temporal scales [GBR (regional-scale), Whitsunday Islands (local-scale) and Keppel Islands/Trunk Reef (temporal)] to examine the effects of scale on the distribution patterns. While SST metrics were important drivers of the distribution of Symbiodinium types at regional and temporal scales, our results demonstrate that spatial variability in water quality correlates significantly with Symbiodinium distribution at local scales. Background levels of Symbiodinium types were greatest at turbid inshore locations of the Whitsunday Islands where SST predictors were not as important. This was not the case at regional scales where combinations of mud and carbonate sediment content coupled with SST anomalies and mean summer SST explained 51.3% of the variation in dominant Symbiodinium communities. CONCLUSIONS/SIGNIFICANCE: Reef corals may respond to global-scale stressors such as climate change through changes in their resident symbiont communities, however, management of local-scale stressors such as altered water quality is also necessary for maintenance of coral-Symbiodinium associations.